Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.7860/jcdr/2014/6510.4006
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcome Among the Retreatment Tuberculosis (TB) Patients Under RNTCP in Chandigarh, India

Abstract: Background: 'RETREATMENT' for Tuberculosis (TB) has long been a neglected area in global TB control. While other components of the Stop TB Strategy have garnered appropriate focus and, increasingly, sufficient resources, issues related to the TB of patients previously treated for tuberculosis remain under examined and under-resourced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 5 publications
1
26
0
Order By: Relevance
“…An increase in the proportion of relapse cases registration under RNTCP after its nationwide implementation in India has been clearly observed. 10,11 The proportion of TAD cases was comparable to other studies done in India which reported that 25% -27% of re-treatment TB cases were TAD cases.…”
Section: 7-9supporting
confidence: 76%
See 2 more Smart Citations
“…An increase in the proportion of relapse cases registration under RNTCP after its nationwide implementation in India has been clearly observed. 10,11 The proportion of TAD cases was comparable to other studies done in India which reported that 25% -27% of re-treatment TB cases were TAD cases.…”
Section: 7-9supporting
confidence: 76%
“…2,10,14 There was one study from West Bengal, India, which reported 22.2% as failure cases among total re-treatment TB cases. 11 The reason for the high proportion of failure cases in Pondicherry may be due to high prevalence of alcohol usage (59%) among TB patients which is consider as important cause for nonadherence to TB treatment.…”
Section: 7-9mentioning
confidence: 99%
See 1 more Smart Citation
“…6 In an earlier study conducted by Sarpal SS et al the mean age of the patients in category II was 35±15.4years. 7 Males 67 (75.28%) outnumbered females 22 (24.72%) in this study. Similar trends have been observed by Jha et al with 1198 (70%) males and 514 (30%) females in the study on retreatment TB cases.…”
Section: Discussionmentioning
confidence: 46%
“…A study [14] also commented that the precision of DMLS is revolutionary with the possibility of creating complicated shapes and geometries with thin sections in a range from 0.02 to 0.03 mm such as required for orthodontics [17, 18], removable partial dentures, maxillofacial prosthesis [19, 20], and intraoral sleep apnoea devices [21]. In addition, many other studies suggested this technique showed great promise as an alternative to the conventional casting technique [7, 12, 22, 23].…”
Section: Introductionmentioning
confidence: 99%